Family Experience Family Experience Caring for the Elderly with Diabetes Mellitus Using Sister Calista Roy's Adaptation Process Approach - Fitriyadi, Junianto; Setyawan, Arif; Pertiwi, Nadia Ayu Elyana (LPPM Universitas dr. Soebandi, 2024)
Introduction: Families who care for the elderly who suffer from diabetes mellitus experience problems in the adaptation process to prevent recurrence and it is difficult to provide an understanding of the condition of the disease to the elderly. The purpose of the study was to describe in detail the experience of families caring for the elderly with diabetes mellitus using a sister calista roy adaptation process approach. Methods: This study uses a qualitative method with a phenomenological study approach. The population of this study were all families living at home with the elderly who suffer from diabetes mellitus in Keling Village, Kepung District with a total sample of 6 participants using purposive sampling technique. The data collection method used in-depth interview techniques. Data analysis technique using Interpretative Phenomenological Analysis. Results: The analysis of this study resulted in the theme of the process of family adaptation to care for the elderly with diabetes mellitus, including: 1) Family stimulation by understanding the condition of the disease and obligations in caring for the patient; 2) Family coping mechanisms by having a patient and calm attitude, and providing effective communication; 3) Family self-regulation by exercising self-control and caring attitude; 4) Family behavior by providing consultation on health services, meeting needs and managing stress. Conclusions: The process of family adaptation in caring for the elderly with diabetes mellitus by reflecting on the behavior of the adjustment process with various kinds of coping that is done to produce an adaptive or maladaptive behavior.